Tinjauan Yuridis Terhadap penjatuhan Pidana Penjara Dibawah Ketentuan Minimum Khusus Dalam Tindak Pidana Narkotika: ( Studi Putusan Nomor 58/Pid.Sus/2022/PN.Jmr ) - purnamasari, oktavia intan; Suyatna (Indonesian Journal of Law and Justice, 2024)
One of the criminal regulations that adheres to a special minimum system is Law Number 35 of 2009 concerning Narcotics, with the threat of a special minimum penalty, the judge may not impose a penalty under the special minimum provisions. In the case of narcotics crime decided by the court, namely in verdict number 58/Pid.Sus/2022/Pn.Jmr, the panel of judges actually imposed punishment under the special minimum provisions. This study aims to determine the consideration of judges in imposing imprisonment under the special minimum provisions in narcotics crimes in decision number 58/Pid.sus/2022/Pn.jmr. in this study using normative juridical research methods with a legal, case, and conceptual approach. Based on the results of this study, the judge in deciding a case should be guided by the laws that have been established and the Supreme Court Circular Letter (SEMA) Number 3 of 2015 as a guideline for the implementation of duties for the court, but the judge in his decision imposed a sentence under a special minimum provision, based on this statement it can be concluded that the judge in imposing imprisonment under a special minimum provision in decision number 58/Pid.Sus/2022/Pn.Jmr is not in line with and contradicts Law Number 35 of 2009 concerning Narcotics and SEMA Number 35 of 2015